The life-cycle and biology of Hemiurus communis Odhner, 1905 (Digenea, Hemiuridae). - Koie, M. (Parasite, 1995)
Previously undescribed cystophorous cercariae which develop in sporocyst germinal sacs in the opisthobranch snail Retusa truncatula (Bruguiére) are shown to be the cercariae of Hemiurus communis Odhner, 1905 (Hemiuridae), a common stomach parasite of non-clupeid fishes off the north-western coasts of Europe. The free-swimming cercaría is ingested by calanoid copepods. The cercarial body is injected into the copepod haemocoel via the delivery tube. The cystophorous cercaria and life-cycle of H. communis are compared with those of other hemiurids from the North-East Atlantic and the known biology of this species is reviewed